К ПОСТРОЕНИЮ АНТРОПОЛОГИИ ПОСТИНДУСТРИАЛЬНОГО ОБЩЕСТВА - МАСАЛОВ, А. Г.; РАК, В. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статье рассматриваются направления и аспекты трансформации индивидуальности в современном мире. Проанализированы основные антропологические концепты «философии постиндустриализма». Анализируется идеологический аспект теории информационного общества. Масалов О.Г., Рак В.А. ДО ПОБУДОВИ АНТРОПОЛОГІЇ ПОСТІНДУСТРІАЛЬНОГО СУСПІЛЬСТВА У статті розглядаються напрями та особливості трансформації індивідуальності у сучасному світі. Проаналізовано основні антропологічні концепти «філософії постіндустріалізму». Аналізується ідеологічний аспект теорії інформаційного суспільства. Ключові слова: «постмодерн», інформаційне суспільство, постіндустріальне суспільство, ідентичність, світогляд, ідеологія. Masalov A. G., Rak V. А. TO THE CONSTRUCTION OF ANTHROPOLOGY OF POSTINDUSTRIAL SOCIETY The article is devoted to the directions and aspects of transformation of a human’s individuality in the modern world. Actuality of the article is conditioned by the situation, when most works on this subject devoted to the technologies, economy and history, while a second-rate role is given to a person. The complex of futurology ideas, dedicated to the radical changes of society, culture and a human under the influence of various technologies was certain as a philosophy of postindustrial society. On the basis of works of row of researchers (D. Bell, E. Toffler, M. Kastels, A. Negri, M. Khardt, J. Attali, A. Zinov’ev and others), basic anthropological konceptions of “philosophy of postindustrialism” were analysed. The possible tendencies of transformation of a human were examined in the context of fragmentary perception of reality, «demassification» of culture, permanent changes of information context, penetration of electronic devices in everyday life, achievements of the gene engineering, transferring of social inequality to the global level. The contradictory tendencies in forming of social identity in the process of informative globalization were defined. The visible contradictions of the universalism and pluralism in information society are removed by transferencing them both in the sphere of pure ideological, and political (through a copula «knowledge» – «power») paradigms, which applicable to the world of things and events depending on situation. The ideological aspect of theory of information society, as a component part of diskurs of power, was analysed in the context of situation of «the end of metanarrations» and in connection with concrete historical and cultural terms. Anthropological prognoses of futurology, considered as: a) a possible conseqence of existent tendencies (prognostic aspect); b) a condition of some groups and parts of society and world on the whole (diagnostic aspect); c) the state of society, desired by some groups (project aspect). The basic konceptions which have a direct relation to the construction of the anthropology of postindustrial society were introducted: «a human as a commodity, creating itself»; «a human, as a product of genetic manipulations»; the koncept of «the kiborg»; «the new nomadism»; «a human in the chaos of information» (contextual «dividuum»). The derections of future actual researches are marked: connection between interactiveness, as asymmetric phenomenon, language, as a tool of the derrivation of meanings, and a power, as a practical expression of the hierarchies of networks, major from which are accessible to the limited number of individuals. Keywords: «postmodern», information society, postindustrial society, identity, «model of reality», ideology, «new nomadism», kiborg.